2019
DOI: 10.1128/mbio.00180-19
|View full text |Cite
|
Sign up to set email alerts
|

A Novel In Vivo Infection Model To Study Papillomavirus-Mediated Disease of the Female Reproductive Tract

Abstract: Papillomaviruses exhibit species-specific tropism, thereby limiting understanding and research of several aspects of HPV infection and carcinogenesis. The discovery of a murine papillomavirus (MmuPV1) provides the opportunity to study papillomavirus infections in a tractable, in vivo laboratory model. MmuPV1 infects and causes disease in the cutaneous epithelium, as well as the mucosal epithelia of the oral cavity and anogenital tract. In this report, we describe a murine model of MmuPV1 infection and neoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(111 citation statements)
references
References 56 publications
12
98
1
Order By: Relevance
“…This broad tropism contrasts with the HPV strains associated with neoplasia, which generally target mucosal or cutaneous tissues and rarely cross-infect [25]. Despite this difference in tropism, MmuPV1 appears to mimic many of the known features of neoplasia associated with more limited HPV strains: MmuPV1 cutaneous papillomas are classic warts, and MmuPV1-induced cervical cancer closely resembles human cervical cancer pathogenesis [5,9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This broad tropism contrasts with the HPV strains associated with neoplasia, which generally target mucosal or cutaneous tissues and rarely cross-infect [25]. Despite this difference in tropism, MmuPV1 appears to mimic many of the known features of neoplasia associated with more limited HPV strains: MmuPV1 cutaneous papillomas are classic warts, and MmuPV1-induced cervical cancer closely resembles human cervical cancer pathogenesis [5,9].…”
Section: Discussionmentioning
confidence: 98%
“…A papillomavirus capable of infecting laboratory mice, MmuPV1, was identified in immune-deficient mice in India in 2010 [5]. This virus has been shown to infect both cutaneous and mucosal tissues [5][6][7], where it can cause both skin and cervical cancer in immune-competent mice-particularly after immune-suppressive UVB irradiation [7][8][9]. In the mouse, deliberate primary infection with MmuPV1 elsewhere has been shown to lead to secondary infection in the oropharynx, at the base of the tongue [10].…”
Section: Introductionmentioning
confidence: 99%
“…These limitations have been overcome by the discovery of the mouse papillomavirus, MmuPV1 or MusPV1, in 2011 [14], the first papillomavirus discovered to infect laboratory mice (Mus musculus). We and others found that MmuPV1 can be used to model infection by high-risk HPVs: 1) MmuPV1 and HPVs encode a similar set of genes and express similar patterns of viral transcripts [15,16]; 2) like HPV, MmuPV1 E6 and E7 genes both play critical roles in pathogenesis [17,18] (manuscript in preparation); 3) MmuPV1 preferentially causes disease in immunocompromised hosts [19][20][21][22] as observed for HPVs in humans; and 4) persistent viral infections lead to cancer in both cutaneous and mucosal sites [20,[23][24][25]. Prior studies of MmuPV1 infection in immunocompetent FVB/N mice showed that persistence of cutaneous papillomas correlated with an immunosuppressive state [20].…”
Section: Introductionmentioning
confidence: 99%
“…While initially found to cause cutaneous warts in immunodeficient mice, MmuPV1 also causes cutaneous warts in immunocompetent strains with or without alterations to their immune system (19,(22)(23)(24)(25)(26)(27). Importantly, MmuPV1 has a wide tissue tropism: it infects not only cutaneous epithelia but also sites typically implicated in the sexual transmission of HPV, including the mucosa of the female and male genitalia, the anus, and oropharyngeal sites (28)(29)(30)(31)(32)(33)(34). We have previously shown that immunocompetent mice experimentally infected with MmuPV1 in their female reproductive tract developed cervical and vaginal cancers (28), much like high-risk HPVs in humans.…”
mentioning
confidence: 99%